#TITLE_ALTERNATIVE# - KUSUMAH (NIM: 23506018); Pembimbing: Dr. Ir. G.A. Putri Saptawati, M.Com., GANSARA
To be able to answer the hypothetical problems in this thesis, the thesis will be analyzing a mapping the role of data mining technology to business intelligence, analytical techniques available in data mining will be maping to the information needs that can be met by business intelligence. Which analysis techniques in data mining is likely can be used by business intelligence. In the business intelligence component there is a component called data warehouse, this component will be analyzed about the relation with the process of extracting information on data mining.